THE IMPACT OF THE ADAPTATION STAGES OF THE PARTIALLY REMOVABLE DENTURES ON THE PROGNOSIS OF THE PROSTHETIC TREATMENT - Roxana Ionela Vasluianu; Raluca Elena Baciu; Cosmin Ionut Cretu; Daniel Paval; Ovidiu Stamatin; Catalina Holban Cioloca; Nicoleta Ioanid; Alice Murariu (Romanian Society of Oral Rehabilitation, 2022)
Oral rehabilitation with removable denture is associated with an increased risk of caries, periodontal disorders, as well as the accentuated resorption of the edentulous ridges, when the adaptation and the forces which are developed on the prosthetic field are not equally distributed. The elements that influence the prognosis of the prosthetic treatment, of the oral rehabilitation, are essential regarding the evolution, from the standpoint of the health of the stomatognat system's parts. The tissues that come into direct contact with removable dentures are the most vulnerable, so there is a significant risk of developing a pathology or a complication of an already existing pathology. The risk of complications is directly proportional to the degree of adaptation of removable dentures. Without a periodic reassessment of the patient and possible maintenance treatments, the health of the tissues of the oral cavity could be deteriorated.